2019
DOI: 10.1108/ijse-12-2017-0623
|View full text |Cite
|
Sign up to set email alerts
|

Gender gap in rice productivity: evidence from Vietnam

Abstract: Purpose The purpose of this paper is to investigate the determinants of the gender gap in the gross value of rice yield in Vietnam. Design/methodology/approach A panel data set of 12 provinces of Vietnam from 2010 to 2014 was used, collected from the Vietnam access to resources household survey. To measure the gender gap in the gross value of rice yield, two-stage least squares and Blinder – Oaxaca decomposition methods were used. Findings The gross value of rice productivity of male-headed households was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Previous researchers have primarily explored factors like employment, working conditions, income, age, and marital status in the examination of gender dynamics within the value chain, and although the favorable impact of cassava selling prices on women's engagement in cassava cultivation was observed, it did not achieve statistical significance; this finding aligns with the outcomes of Van et al (2018), which identified that women's participation in value chain was influenced by educational attainment, the count of dependents and credit accessibility.…”
Section: The Determinants Affecting Women's Choice To Engage In Cassa...mentioning
confidence: 90%
“…Previous researchers have primarily explored factors like employment, working conditions, income, age, and marital status in the examination of gender dynamics within the value chain, and although the favorable impact of cassava selling prices on women's engagement in cassava cultivation was observed, it did not achieve statistical significance; this finding aligns with the outcomes of Van et al (2018), which identified that women's participation in value chain was influenced by educational attainment, the count of dependents and credit accessibility.…”
Section: The Determinants Affecting Women's Choice To Engage In Cassa...mentioning
confidence: 90%
“…It has been shown that the elderly and the young are not active income generators and cannot do hard work in the farm sector. Larger households indicate elderly and adolescent individuals (Van Tran et al, 2019) and therefore a lower value of per capita output in the agricultural sector. Younger members of farm households also attend school and hence cannot participate actively in income generation, yielding a negative effect on household income.…”
Section: Impact Of Nonfarm Income On Agricultural Productivitymentioning
confidence: 99%
“…Many studies have focused on the issue of gender gap in agriculture (Van Tran et al, 2018;Ali et al, 2016;Elahi et al, 2020) and livestock sectors (Debela, 2017;Elahi et al, 2019a). In Ethiopia, a few studies have examined learning achievement gaps in primary and secondary education (Sanfo and Ogawa, 2021;Tesema and Braeken, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on the issue of gender gap in agriculture (Van Tran et al. , 2018; Ali et al.…”
Section: Introductionmentioning
confidence: 99%